2016
DOI: 10.17957/ijab/15.0233
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Wheat Flour Infestation by some Insects on its Quantity and Quality Loss, Fungal Contamination and Mycotoxins

Abstract: Wheat flour samples were artificially infested with Corcyra cephalonica, Ephestia kuehniella, Tribolium confusum (separately) and with the three insect populations together. The effect of insects' infestation on wheat flour quantity and quality loss, fungal contamination and presence of mycotoxins was studied after two months of storage (25±2 o C and 65%RH). Wheat flour infested with insects was sieved into two portions (sieved and residual flour) after insects populations have been recorded. The results revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…These agreed with that obtained by Ahmadi et al (21) who found that gamma radiation significantly affect the nutritional indices of T. castaneum. Moreover, Gabarty and Abou El Nour (22) studied the effect of artificially infestation of 3KGy irradiated flour with Corcyra cephalonica, Ephestia kuehniella, T. confusum, they declared that there were major alterations in the insects population and high weight loss and lowering of the nutritional composition of the flour.…”
Section: Discussionmentioning
confidence: 99%
“…These agreed with that obtained by Ahmadi et al (21) who found that gamma radiation significantly affect the nutritional indices of T. castaneum. Moreover, Gabarty and Abou El Nour (22) studied the effect of artificially infestation of 3KGy irradiated flour with Corcyra cephalonica, Ephestia kuehniella, T. confusum, they declared that there were major alterations in the insects population and high weight loss and lowering of the nutritional composition of the flour.…”
Section: Discussionmentioning
confidence: 99%
“…The level of AB 1 and AB 2 were checked all in wheat flour samples. These findings documented the role of insects in infestation of wheat flour through aflatoxigenic fungi in storage system (Gabarty & El Nour, 2016) [19] . Insects, fungi and aflatoxin contamination are previously discussed in detailed in maize plant.…”
Section: Mycotoxin Accumulation In Storage Areasmentioning
confidence: 56%
“…The wheat flour stored in PP bags was infested by T. castaneum, and the population increased with storage time. Tribolium castaneum is well known as a pest of wheat flour stocks [ 10 , 13 , 20 ]. The development of insects in PP bags was due to favorable environmental conditions such as high humidity [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Through its feeding activities, T. castaneum affects the quality of the wheat flour, including fatty acids, proteins, and gluten. The presence of T. castaneum can also result in the development of toxins such as benzoquinones and aflatoxins [ 13 , 20 ]. In addition, parts of dead insects can affect the quality of the wheat flour by increasing its water content, microbial fauna, and uric acid content, as well as changing the color of the flour [ 23 ].…”
Section: Discussionmentioning
confidence: 99%